Effects of haemodynamically atrio‐ventricular optimized His bundle pacing on heart failure symptoms and exercise capacity: the His Optimized Pacing Evaluated for Heart Failure (HOPE‐HF) randomized, double‐blind, cross‐over trial. (23rd February 2023) - Whinnett, Zachary I.; Shun‐Shin, Matthew J.; Tanner, Mark; Foley, Paul; Chandrasekaran, Badri; Moore, Philip; Adhya, Shaumik; Qureshi, Norman; Muthumala, Amal; Lane, Rebecca; Rinaldi, Aldo; Agarwal, Sharad; et al.
Abstract: Aims: Excessive prolongation of PR interval impairs coupling of atrio‐ventricular (AV) contraction, which reduces left ventricular pre‐load and stroke volume, and worsens symptoms. His bundle pacing allows AV delay shortening while maintaining normal ventricular activation. HOPE‐HF evaluated whether AV optimized His pacing is preferable to no‐pacing, in a double‐blind cross‐over fashion, in patients with heart failure, left ventricular ejection fraction (LVEF) ≤40%, PR interval ≥200 ms and either QRS ≤140 ms or right bundle branch block. Methods and results: Patients had atrial and His bundle leads implanted (and an implantable cardioverter‐defibrillator lead if clinically indicated) and were randomized to 6 months of pacing and 6 months of no‐pacing utilizing a cross‐over design. The primary outcome was peak oxygen uptake during symptom‐limited exercise. Quality of life, LVEF and patients' holistic symptomatic preference between arms were secondary outcomes. Overall, 167 patients were randomized: 90% men, 69 ± 10 years, QRS duration 124 ± 26 ms, PR interval 249 ± 59 ms, LVEF 33 ± 9%. Neither peak oxygen uptake (+0.25 ml/kg/min, 95% confidence interval [CI] −0.23 to +0.73, p = 0.3) nor LVEF (+0.5%, 95% CI −0.7 to 1.6, p = 0.4) changed with pacing but Minnesota Living with Heart Failure quality of life improved significantly (−3.7, 95% CI −7.1 to −0.3, p = 0.03). Seventy‐six percent of patients preferred His bundle pacing‐on and 24% pacing‐off ( p < 0.0001). Conclusion: His bundle pacing did not increase peak oxygen uptake but, under double‐blind conditions, significantly improved quality of life and was symptomatically preferred by the clear majority of patients. Ventricular pacing delivered via the His bundle did not adversely impact ventricular function during the 6 months. Abstract : PR prolongation impairs atrio‐ventricular (AV) coupling: reducing left ventricular (LV) pre‐load and stroke volume, and worsening symptoms. His bundle pacing allows AV delay shortening while maintaining normal ventricular activation. HOPE‐HF evaluated whether AV optimized His pacing is preferable to no‐pacing, in randomized double‐blind cross‐over fashion. BP, blood pressure; LVEF, left ventricular ejection fraction; MLWHF, Minnesota Living With Heart Failure; QOL, quality of life; QRSd, QRS duration; RBBB, right bundle branch block; SBP, systolic blood pressure.